Study on the tensile modulus of seamless fabric and tight compression finite element modeling. Issue 1 (January 2020) - Wu, Jiahong; Jin, Zimin; Jin, Jing; Yan, Yuxiu; Tao, Jianwei
Tight compression garments are able to exert pressure on the surface of the human body, helping to relieve muscle fatigue and accelerate recovery. In order to study the effect of the tensile property on fabric pressure on the human body, by response surface methodology, in this paper 13 seamless knitting fabrics were designed with various knitting parameters, including the linear density of bare elastic yarn (33.3, 55.6 and 77.8 dtex), yarn feed tension (0.015, 0.030 and 0.045 cN/dtex) and fabric structure (1 × 1 mock rib, cross-float and plain stitch). Through tensile testing, the tensile moduli of 13 fabrics were measured and the effect of knitting parameters was analyzed. In addition, a finite element method was used to simulate the tight pressure on the human thigh of fabrics with different tensile moduli with ANSYS workbench 19.0. Furthermore, an actual pressure experiment was designed to prove the accuracy and validation of the simulation. The result showed that the effect of yarn feed tension on the elasticity modulus was the least significant, while linear density and structure had a great influence. A quadratic response surface regression model of the elasticity modulus was created, which could calculate a bare elastic yarn knitting fabric by using its parameters. It was proved that the finite element model was able to predict pressure accurately. Through the pressure numerical simulation of three fabric samples with different tensile moduli (0.111, 0.253 and 0.523 MPa), it was indicated that for fabric with a low tensile modulus, its tight compression merely changed as elongation increased; however, for fabric with a high tensile modulus, tight compression was promoted as elongation increased.